Two isoforms of the Notch antagonist Hairless are produced by differential translation initiation. - Maier, D.; Nagel, A.C.; Preiss, A. (Proceedings of the National Academy of Sciences of the United States of America, 2002)
The Notch-signaling pathway controls cellular differentiation, including proliferation and cell death in all higher metazoans (including flies and men). Signal transduction through activated Notch involves the CSL group of transcriptional regulators. Notch signals need to be tightly regulated, and in Drosophila they are antagonized by the Hairless (H) protein. H silences the activity of Notch target genes by transforming the Drosophila CSL protein, Suppressor of Hairless [Su(H)], from a transcriptional activator into a repressor while recruiting one of the corepressors dCtBP or Groucho. The H protein has a calculated molecular mass of approximately 110 kDa and contains several functional domains apart from the two small corepressor-binding domains. However, although there is no indication for alternative splicing, two Hairless protein isoforms, H(p120) and H(p150), are observed throughout development. Here, we show that the smaller isoform derives from an internal ribosome entry site (IRES) within the ORF. The IRES is active in a heterologous assay and contains an essential, conserved structural element. The two Hairless isoforms have residual activity in vivo which is, however, reduced compared to a combination of both, which implies that both protein isoforms are necessary for WT function. In larval tissues, translation of the two isoforms is cell-cycle regulated: whereas the H(p150) isoform is translated during interphase, H(p120) is enriched during mitosis. Thus, the presence of either H isoform throughout the cell cycle allows efficient inhibition of Notch-regulated cell proliferation.